Analysis of Benefits and Costs of Developing Technology Services for Provision of Transportation Facilities and Official Accommodation and Employee Leave at PT Bukit Makmur Mandiri Utama (BUMA) - Supriyanto, Rahmat Eko (Journal of Current Research In Multidisciplinary, 2024)
BUMA is striving to enhance the service of transportation facilities and assistance, as well as employee travel and leave accommodations, by incorporating technology into self-service reservations and conducting a cost-benefit analysis to gauge the initiative's profitability. This study uses a descriptive quantitative approach, starting from collecting information, interpreting the data obtained, observing the process, and identifying all things related to finance, such as costs (direct and indirect) and benefits (tangible and intangible). The researcher computes the expenses and advantages to ascertain the viability of the investment. The techniques used in financial calculations are NPV, payback period, and ROI. The financial analysis yielded an NPV of Rp 482,542,605.58, signifying that BUMA is prepared to invest in information technology. ROI provides 438% benefits, indicating that there is a feasible profit from the investment. A payback period (PP) of 0.23, or less than one year, demonstrates the feasibility of this investment by allowing for a relatively short return on investment capital. This analysis concludes that the system's use significantly accelerates the provision of transportation facilities and assistance, as well as facilitates employee travel and leave accommodations. Employees can observe these benefits in the efficient use of time and resources, the system's user-friendliness, and the potential savings on reservation and travel management expenses.